A study about the variable of WAVING in Japanese finswimmers in the 50-m surface and apnea - Oshita, K.; Ross, M.; Koizumi, K.; Kashimoto, S.; Takahashi, K.; Kawakami, M. (1st International Scientific Conference of Aquatic Space Activities, 2008)
We investigated about the variables of WAVING, such as the swimming velocity (SV), the WAVING rate (WR; WAVING per second), the WAVING length (WL; distance per WAVING) in the 50-m Surface (SF) and Apnea (AP). The subjects were five expert (EX) and four nonexpert males (NE). The SV of EX was faster than that of NE in the SF (2.7 vs. 2.3 m/ sec) and the AP (3.1 vs. 2.6 m/ sec). The WL of EX was longer than that of NE in the SF (1.0 vs. 0.9 meter) and the AP (1.1 vs. 1.0 meter). The WR in the SF and the AP were not significant difference between EX (2.8 and 2.7 Hz) and NE (2.7 and 2.6 Hz). Moreover, there was a significant positive relationship between SV and WL in the SF or the AP. However, there was no significant relationship between SV and WR in the SF or the AP. These results suggest that WL is concluded to be an important factor that influences the SV in the 50-m SF and AP.